Subject-Controlled, On-demand, Dorsal Genital Nerve Stimulation to Treat Urgency Urinary Incontinence; a Pilot - van Breda, Hendrikje M. K.; Farag, Fawzy F.; Martens, Frank M. J.; Heesakkers, John P. F. A.; Rijkhoff, Nico J. M. (Frontiers in Neuroscience, 2016)
Objectives To evaluate the effect of subject-controlled, on-demand, dorsal genital nerve stimulation on non-neurogenic urgency urinary incontinence in a domestic setting. Materials and Methods Non-neurogenic patients >18 years with overactive bladder symptoms and urgency urinary incontinence were included. Exclusion criteria were mainly stress urinary incontinence. Patients underwent one week of subject-controlled, on-demand, dorsal genital nerve stimulation, delivered by a percutaneously placed electrode near the dorsal genital nerve connected to an external stimulator (pulse-rate 20 Hz, pulse-width 300 μs). Patients activated the stimulator when feeling the urge to void and stimulated for 30 s. The amplitude was set at the highest tolerable level. A bladder diary including a severity score of the urgency urinary incontinence episodes/void (scores: 0=none, 1=drops, 2=dashes, 3=soaks) and a padtest was kept 3 days prior to, during, and 3 days after the test period. The subjective improvement was also scored. Results Seven patients (4 males / 3 females) were enrolled, the mean age was 55 years (range 23-73). Six completed the test week. In the remaining patient the electrode migrated and was removed. 5/6 finalized the complete bladder diary, 1/6 recorded only the heavy incontinence episodes (score=3). 4/6 completed the padtest. In all patients who finalized the bladder diary the number of urgency urinary incontinence episodes decreased, in 3/5 with ≥60%. The heavy incontinence episodes (score=3) were resolved in 2/6 patients, and improved ≥ 80% in the other 4. The severity score of the urgency urinary incontinence episodes/void was improved with ≥60% in 3/5 patients. The mean subjective improvement was 73%. Conclusion This feasibility study indicates that subject-controlled, on-demand dorsal genital nerve stimulation using a percutaneously placed electrode is possible over a longer time period, in a home setting, with a positive effect on non-neurogenic overactive bladder symptoms with urgency urinary incontinence. Although the placement is an easy procedure, it is difficult to fixate the electrode to keep it in the correct position. Improvements in hardware, like a better fixated electrode and an easy to control stimulator, are necessary to make SODGNS a treatment possibility in the future.